UNIT 4.70 Synthesis of 5′‐Aldehyde Oligonucleotide. Issue 1 (1st March 2016) - Lartia, Rémy
Abstract : Synthesis of oligonucleotide ending with an aldehyde functional group at their 5′‐end (5′‐AON) is possible for both DNA (5′‐AODN) and RNA (5′‐AORN) series irrespectively of the nature of the last nucleobase. The 5′‐alcohol of on‐support ODN is mildly oxidized under Moffat conditions. Transient protection of the resulting aldehyde by N, N′ ‐diphenylethylenediamine derivatives allows cleavage, deprotection, and RP‐HPLC purification of the protected 5′‐AON. Finally, 5′‐AON is deprotected by usual acetic acid treatment. In the aggregates, 5′‐AON can be now synthesized and purified as routinely as non‐modified ODNs, following procedures similar to the well‐known "DMT‐On" strategy. © 2016 by John Wiley & Sons, Inc.